Overcoming Global Problems And Development Strategies (Texas Journal of Philology, Culture and History, 2026)
The article expresses an opinion about globalization processes in today's world, in particular, youth education and social protection of the needy in the family, neighborhood and educational institutions, strengthening the idea of patriotism through pedagogical education.